Firefly Hollow - McGhee, Alison 1960-; Denise, Christopher (New York : Atheneum Books for Young Readers, 2014)
Because their dreams of daring adventures go against the cautious teachings of their nations, Firefly and Cricket set out on their own, find a home with kindly Vole, and together help a grieving "miniature giant" named Peter.
Keywords: Fireflies -- Fiction; Crickets -- Fiction; Voles -- Fiction; Friendship -- Fiction; Adventure and adventurers -- Fiction; Grief -- Fiction